How to Use Traps to Catch Nuisance Wildlife in Your Yard - Holly K. Ober; Arlo Kane (EDIS, 2012)
When wildlife become a nuisance in your yard, there are three general approaches you can take: make habitat modifications, use deterrents, or trap animals. In most residential settings, making habitat modifications or using deterrents will be both simpler and more effective than trapping. But trapping is warranted in certain situations when trying to solve conflicts between people and wildlife. This 6-page fact sheet provides information on stopping wildlife damage through the use of trapping. Written by Holly K. Ober and Arlo Kane, and published by the UF Department of Wildlife Ecology and Conservation, October 2012.